The Implementation of Cash Waqf Linked Deposit by Islamic Banking (Case Study of Bank Muamalat) - Cheryl Patriana Yuswar; Atharyanshah Puneri (Fiat Justisia: Jurnal Ilmu Hukum, 2025)
The implementation of cash waqf in Indonesia, with a particular focus on Cash Waqf Linked Deposit (CWLD) as the latest Islamic banking product in the country’s Islamic financial sector. The study adopts a normative legal research method and utilizes primary data obtained through an online interview with PT Bank Muamalat Indonesia Tbk. The data is analyzed using a descriptive-qualitative approach. The findings reveal that although the Indonesian Waqf Board estimates the potential of the cash waqf sector at 180 trillion Rupiah, actual realization remains significantly low, with only 2.3 trillion Rupiah collected as of 2023. In response to this gap, the Financial Services Authority (OJK) introduced CWLD in October 2024 as a strategic effort to strengthen Islamic banking and promote greater public participation in cash waqf. PT Bank Muamalat, as Indonesia’s first appointed Islamic Financial Institution to Receive Cash Waqf (LKS-PWU), plans to implement CWLD as part of its new sharia-compliant investment services. As a recently introduced product, CWLD at Bank Muamalat is expected to attract increasing interest from the Indonesian public in the years ahead.